The winds of autumn eaudiobook Seasons of the heart (oke) series, book 2. - Oke, Janette (Seasons of the Heart, 2003)
Pioneering inspirational author and perennial best-seller Janette Oke is renowned for her touching novels of faith and virtue. The Winds of Autumn is the continuation of the heartwarming family saga begun in Once Upon a Summer (K1041). On the brink of manhood, Josh lives with his Aunt Lou and spends all his time studying or fishing. When a new teacher arrives at his school, Josh prospers under his tutelage. Meanwhile, the teacher's beautiful daughter begins to stir new feelings in Josh. Listeners will cherish this tale of life and new love.